Extraordinary Aggressive Behavior from the Giant Coral Reef Fish, Bolbometopon muricatum, in a Remote Marine Reserve - Muñoz, Roldan C.; Zgliczynski, Brian J.; Laughlin, Joseph L.; Teer, Bradford Z. (PLOS ONE, 2012)
Human impacts to terrestrial and marine communities are widespread and typically begin with the local extirpation of large-bodied animals. In the marine environment, few pristine areas relatively free of human impact remain to provide baselines of ecosystem function and goals for restoration efforts. Recent comparisons of remote and/or protected coral reefs versus impacted sites suggest remote systems are dominated by apex predators, yet in these systems the ecological role of non-predatory, large-bodied, highly vulnerable species such as the giant bumphead parrotfish (Bolbometopon muricatum) has received less attention. Overfishing of Bolbometopon has lead to precipitous declines in population density and avoidance of humans throughout its range, contributing to its status as a candidate species under the U. S. Endangered Species Act and limiting opportunities to study unexploited populations. Here we show that extraordinary ecological processes, such as violent headbutting contests by the world’s largest parrotfish, can be revealed by studying unexploited ecosystems, such as the coral reefs of Wake Atoll where we studied an abundant population of Bolbometopon. Bolbometopon is among the largest of coral reef fishes and is a well known, charismatic species, yet to our knowledge, no scientific documentation of ritualized headbutting exists for marine fishes. Our observations of aggressive headbutting by Bolbometopon underscore that remote locations and marine reserves, by inhibiting negative responses to human observers and by allowing the persistence of historical conditions, can provide valuable opportunities to study ecosystems in their natural state, thereby facilitating the discovery, conservation, and interpretation of a range of sometimes remarkable behavioral and ecological processes.